RANCANG BANGUN RFID ABSENSI PEGAWAI KANTOR DESA SOSOPAN KECAMATAN KOTAPINANG - Hermadi, Heru Pangestu; Herdianto (CV. Hawari, 2023)
The development of science and technology is currently growing very rapidly from time to time. the application of various existing technologies encourages the development of work efficiency and service quality in companies, government agencies, and the world of education. The development of information technology can improve performance, including employee absences. Recording employee absences is an important factor in human resource management. In-depth and detailed information about the presence of an employee can determine work performance, salary, productivity or progress of the institution in general. The Sosopan Village Office, Kotapinang District, still uses manual attendance, and therefore requires a system that can increase efficiency, including what will be made, namely Arduino-based Employee Attendance RFID, attendance is only for data that has been registered. The purpose of this research is to make it easier for every employee. office and help the admin to record every attendance.